Learning Video Making Training Multimedia Based Using Powtoon For Teachers Of State 12 Junior High School, Sungai Raya, Regency. Kuburaya - Sujatmiko, Wandi (Society : Jurnal Pengabdian Masyarakat, 2023)
Education is a real effort to facilitate other individuals in achieving independence and mental maturity so that they can survive in the competition of life. In educational activities, students are targets (objects) and at the same time as educational subjects. In Tilaar's perspective, multicultural education originated from the development of the idea of "interculturalism" after World War II. The emergence of the idea and awareness of "interculturalism" is related to developments in international politics concerning human rights, independence from colonialism and discrimination. Along with the progress of the development of Information Technology, globalization is also becoming increasingly rapid. As it is known that globalization has brought many foreign cultures to Indonesia. Information Technology sometimes unwittingly changes its function to become a foreign cultural tool. The purpose of this Community Service Activity is to provide Training on Making Multimedia-Based Learning Videos Using Powtoon for SMP Negeri 12 teachersKeywords : Video, Multimedia, Powtoon, Training.